ENVIRONMENTAL CONCERN: DOES IT DRIVE GREEN PURCHASE INTENTION OF SUSTAINABLE PACKAGING? - Mongula, Angelline; Masnita, Yolanda; Kurniawati, Kurniawati (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
The growing importance of environmental concern as a critical issue has recently increased. Lower environmental damage raises consumer awareness of the importance of environmental preservation. Environmental concern triggers consumers